Badanie regionalnego zróżnicowania sytuacji ekonomiczno-finansowej banków spółdzielczych w Polsce z wykorzystaniem metod taksonomicznych - Siudek, Tomasz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2006)
Using cluster analysis and factor analysis, three regions of Poland presenting different characteristics of financial standing of cooperative banks were selected, namely: the southern, the western and the central-eastern. According to the efficiency ratio levels, the leading best banks were located in the western region, according to financial liquidity – in the southern region, and in respect to solvency and capital adequacy – in the central-eastern region respectively. The difference in the dynamics of banks’ assets between selected regions was not statistically significant